Rewilding abandoned landscapes in europe : biodiversity impact and contribution to human well-being - Navarro, Laetitia Marie Lucie, 1983- (2014)
Tese de doutoramento, Biologia (Biologia da Conservação), Universidade de Lisboa, Faculdade de Ciências, 2014